Carbon quantum dots/TiO2 nanocomposite for sensing of toxic metals and photodetoxification of dyes with kill waste by waste concept. (5th October 2018) - Mehta, Akansha; Mishra, Amit; Kainth, Shagun; Basu, Soumen
Abstract: The exposure of even low amount of heavy metals and industrial dyes in wastewater leads to cardiovascular, neurological and developmental disorders. Consequently, millions of inorganic and organic pollutants containing toxic heavy metals have been accounted as water contaminants. In this report, a novel approach has been designed based on the methodology to "kill waste by waste". Firstly the toxic metals like lead (Pb) ions were detected using fluorescence carbon quantum dots (CQDs) and after impregnation of TiO2 into the same Pb-CQDs composite, it was further used for photodegradation of harmful industrial dyes. The CQDs have been designed as a nanosensor for Pb ion detection and its fluorescence is effectively quenched with good sensitivity (0.070 μM) and selectivity. This Pb-CQDs solution was further immersed in TiO2 by wet impregnation method to fabricate Pb-CQDs-TiO2 (PCT) nanocomposite with a change in the energy gap (3.2 to 2.8 eV) making the composite active in visible light irradiation. The degradation efficiency achieved 100% mark for RBX dye and 1.8 μmols of CO2 evolution was observed in 60 min. The plausible mechanism is proposed based on GCMS studies suggesting the formation of intermediates like triazine and aryl sodium sulphonates before complete decomposing into CO2 and water. Graphical abstract: Unlabelled Image Highlights: A novel "kill waste by waste" approach was developed for detection of heavy metals by carbon quantum dots. Lead sensing and deposition on TiO2 - carbon quantum dots was preferred over other toxic metals. The lead deposited TiO2 -carbon quantum dots nanocomposites completely mineralized the industrial dyes to CO2 and H2 O. The nanocomposites was effective for the treatment of real waste water samples.